Implementation of Geogebra Application Media in Improving the Work Results of Three-Dimensional Mathematics Subjects in Class XII MIPA B Man 1 Bandung City - Lilis Widianti (PT Publikasiku Academic Solution, 2023)
The purpose of this study is to determine the implementation of geogebra application media in improving the learning outcomes of three-dimensional material subjects in class XII MIPA B MAN 1 Bandung City. The problem faced by teachers is that students still have difficulty in visualizing building space, especially understanding the concept of distance in building three-dimensional space. Student learning outcomes, it is known that the average class score on space building material is 53.47, this does not meet the Minimum Completeness Criteria (KKM). The research method used is classroom action research, which makes continuous improvements to the learning process through the stages of planning, implementation, observation and reflection. The results of the study found that in cycle 1, student learning outcomes increased to 27.40% who met the criteria, while in cycle 2 increased to 75.70% of students meeting the minimum completeness criteria. It should be noted that the use of the geogebra application requires hardware devices such as laptops and mobile phones, if all students can provide their devices, then all students can try the application on their respective devices.